The risk of viral transmission in feed: What do we know, what do we do?. Issue 6 (10th July 2020) - Dee, Scott A.; Niederwerder, Megan C.; Patterson, Gil; Cochrane, Roger; Jones, Cassie; Diel, Diego; Brockhoff, Egan; Nelson, Eric; Spronk, Gordon; Sundberg, Paul
Abstract: The role of animal feed as a vehicle for the transport and transmission of viral diseases was first identified in 2014 during the porcine epidemic diarrhoea virus epidemic in North America. Since the identification of this novel risk factor, scientists have conducted numerous studies to understand its relevance. Over the past few years, the body of scientific evidence supporting the reality of this risk has grown substantially. In addition, numerous papers describing actions and interventions designed to mitigate this risk have been published. Therefore, the purpose of this paper is to review the literature on the risk of feed ( what do we know) and the protocols developed to reduce this risk ( what do we do ) in an effort to develop a comprehensive document to raise awareness, facilitate learning, improve the accuracy of risk assessments and to identify knowledge gaps for future studies.